New records of water mite (Acari: Hydrachnidia) species for the Turkish fauna - Esen, Yunus; Pesic, Vladimir; Citil, Cihan; Erman, Orhan (Tubitak Scientific & Technological Research Council Turkey, 2012)
Four species of water mites (Acari: Hydrachnidia) are presented for the fauna of Turkey. Oxus (s. str.) angustipositus Viets, 1908; O. (s. str.) hastatus (Lundblad, 1954); Frontipodopsis (s. str.) reticulatifrons Szalay, 1945; and Hungarohydracarus subterraneus Szalay, 1943 are new records for the Turkish fauna. The description of the male O. (s. str.) hastatus, a species known for a single female specimen from Portugal, is given for the first time. Frontipodopsidae and Hungarohydracaridae are reported for the first time for Turkey.
Türkiye faunası için yeni su kenesi (Acari: Hydrachnidia) türleri
Keywords: Water mite; Acari; new records; running waters; hyporheic habitats; Turkey